Structured Catalysts for Non-Thermal Plasma-Assisted Ammonia Synthesis - Eugenio Meloni; Liberato Cafiero; Marco Martino; Vincenzo Palma (Energies, 2023)
Ammonia has been intensively studied as a clean, sustainable fuel source and an efficient energy storage medium due to its effectiveness as a hydrogen carrier molecule. However, the currently used Haber–Bosch process requires a large fossil fuel input, high temperatures and pressures, as well as a significant capital investment. These constraints prevent decentralized and small-scale ammonia production at the level of small farms and local communities. Non-thermal plasma (NTP) can promote ammonia synthesis in operating conditions in which, in a conventional process, a catalyst is generally not active. In this study, the production of NTP-assisted catalytic ammonia at milder temperatures and ambient pressure was investigated. Four different structured catalysts were prepared and tested using an experimental plant based on a dielectric barrier discharge (DBD) reactor. The effect of the gas hourly space velocity (GHSV) was investigated, as well as the effect of the N2/H2 ratio on catalyst performance. The results evidenced that the best catalytic activity (about 4 mmol h−1 of produced NH3) was obtained using the 10Ni/zeolite 13X sample with the lowest energy consumption, thus highlighting the feasibility of this innovative technology in this field.